PATIENT SATISFACTION WITH PHYSICAL THERAPY SERVICES AND ASSOCIATED FACTORS AT THE DEPARTMENT OF PAIN MANAGEMENT - PHYSICAL THERAPY - TRADITIONAL MEDICINE, TRUNG VUONG HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of satisfaction and analyze some factors related to the satisfaction of patients receiving physical therapy at the Department of Pain Management - Physical Therapy - Traditional Medicine, Trung Vuong Hospital in 2025.Method: Cross-sectional study in 2025 at the Department of Pain Treatment - Physical Therapy - Traditional Medicine; scale based on SERVPERF/PSS; descriptive and regression analysis (p < 0.05).Results: Female 58.8%; ≥ 60 years old 69.3%; residing in Ho Chi Minh city 64.2%; using health insurance 97.8%. Overall satisfaction: very good 49.2%, good 40.3%, normal 10.5%. By dimension: guaranteed very good 59.4%; trust 58.2%; facilities 48.6% (normal 13.4%; poor 1.6%); responsive 43.8% (normal 16.3%; poor 2.6%). Associated factors: ≥ 60 years old (OR = 6.52; p < 0.05), no longer working (97.0% vs 76.5%; p < 0.05), treatment duration > 1 month (97.4%) associated with higher satisfaction.Conclusion: High satisfaction, outstanding in “assurance”, “trust”, “sympathy”. Need to prioritize improving “responsiveness” and “facilities”, and standardizing communication friendly to the elderly/low education.
Keywords: Patient satisfaction, physical therapy, service quality, Trung Vuong.